Creme Brulee II / Nor Azhar Mohd Taib ... [et al.] - Mohd Taib, Nor Azhar; Ismail, Saidah; Md Isa, Haslinda; Abdul Malek, Mohd Ridzuan (UiTM Press, 2023)
This book is specifically written for students who will be taking French as a third language at Universiti Teknologi MARA. Creme Brulee II introduces the basis for learning the French language. It is an introduction to the French language and suitable for beginners. It was written to meet the needs of 28 teaching hours in one semester. This book contains four basic topics which are Nous Sommes Lundi, Mes preferences, Bon Voyage, and Le Shopping. Each topic consists of a dialogue, followed by notes on vocabulary, grammar, culture and proverbs. Exercises and samples of test questions are also included to reinforce students' understanding. Creme Brulee II starts with the basic needs of students and puts them in everyday situations. Thus, they will be able to participate in basic French conversations, such as talking about their birthdays, preferences, travelling and shopping. This will give them the necessary tools for immediate communication.